Causal linkage of tobacco smoking with ageing: Mendelian randomization analysis towards telomere attrition and sarcopenia. Issue 2 (25th January 2023) - Park, Sehoon; Kim, Seong Geun; Lee, Soojin; Kim, Yaerim; Cho, Semin; Kim, Kwangsoo; Kim, Yong Chul; Han, Seung Seok; Lee, Hajeong; Lee, Jung Pyo; Joo, Kwon Wook; Lim, Chun Soo; et al.
Abstract: Background: Ageing traits and frailty are important health issues in modern medicine. Evidence supporting the causal effects of tobacco smoking on various ageing traits is required. Methods: This study performed Mendelian randomization (MR) analysis instrumenting 377 genetic variants associated with being an ever‐smoker at a genome‐wide significance level to test the causal estimates from tobacco smoking. The outcome data were obtained from 337 138 white British ancestry participants from the UK Biobank. Leucocyte telomere length, appendicular lean mass index, subjective walking pace, handgrip strength,  and wristband accelerometry‐determined physical activity degree were collected as ageing‐related outcomes. Summary‐level MR analysis was performed using the inverse variance‐weighted method and pleiotropy‐robust MR methods, including weighted median and MR‐Egger. Observational association between the outcome traits and phenotypically being an ever‐smoker was also investigated. Results: Summary‐level MR analysis indicated that a higher genetic predisposition for tobacco smoking was significantly associated with shorter leucocyte telomere length (twofold increase in prevalence of smoking towards standardized Z‐score, −0.041 [−0.054, −0.028]), lower appendicular lean mass index (−0.007 [−0.010, −0.005]), slower walking pace (ordinal category, −0.047 [−0.054, −0.033]) and lower time spent on moderate‐to‐vigorous physical activity (hours per week, −0.39 [−0.56, −0.23]). The causal estimates were non‐significant towards handgrip strength phenotype (kg, 0.074 [−0.055, 0.204]). Pleiotropy‐robust MR results generally supported the main causal estimates. The observational findings also showed significant association between being an ever‐smoker and the ageing traits. Conclusions: Genetically predicted and observational tobacco smoking status are significantly associated with poor ageing phenotypes. Healthcare providers may continue to reduce tobacco use, which may be helpful in reducing the burden of ageing and frailty.